The development in self-understanding of the CCAP Nkhoma Synod as church during the first forty years of autonomy : an ecclesiological study - Brown, Walter Lawrence (Stellenbosch : University of Stellenbosch, 2006)
Thesis (DTh (Systematic Theology and Ecclesiology))--University of Stellenbosch, 2005.